Evaluation of PAWP and PLC? Expression in Infertile Men with Previous ICSI Fertilization Failure - Azad, Nahid; Nazarian, Hamid; Nazari, Leila; Ghaffari Novin, Marefat; Piryaei, Abbas; Heidari, Mohammad Hassan; Masteri Farahani, Reza; Sadjadpour, Seyedeh Susan (Urology Journal, 2018)
Purpose: The aim of this study was to evaluate postacrosomal sheet WW domain binding protein (PAWP) and phospholipase C ? (PLC?) protein expression in patients with fertilization failure. Materials and Methods: Semen samples were collected from 15 fertile men (control group) and 15 patients with previous fertilization failure following ICSI (FF group) and were analyzed according to World Health Organization (WHO) criteria. The mean percentages of PAWP and PLC? positive sperm and the total level of PAWP and PLC? proteins were assessed using immunofluorescence staining. Results: A significantly lower level and lower percentage of PAWP positive sperm in patients with fertilization failure was found compared to the control group (P = 0.01 and P = 0.03, respectively). The mean percentage of PLC? positive sperm and level of PLC? protein were significantly lower in FF group compared to the control group (P = 0.0003 and P = 0.04, respectively). Significant positive correlations was observed between PAWP and PLC? positive sperms (r = 0.4, P = 0.008) and also total level of expression of PLC? and PAWP proteins (r = 0.4, P = 0.02) in all participants in the study. Conclusion: This is the first study that evaluates two main candidates for sperm-borne oocyte activating factors (SOAFs) simultaneously in patients with fertilization failure. Considering lower expression of PAWP and PLC? proteins in such patients, it seems like both factors might have the potential to be considered as SOAFs and diagnostic markers for the oocyte activation ability.